Essential Infantile Esotropia: A Course of Treatment From Our Experience - Pensiero, Stefano; Diplotti, Laura; Presotto, Marianna; Ronfani, Luca; Barbi, Egidio (Frontiers in Pediatrics, 2021)
Background: Essential infantile esotropia (EIE) is the most common type of childhood esotropia. Although its classical approach is surgical, less invasive techniques have been proposed as an adjunct or alternative to traditional surgery. Among them, chemodenervation with botulinum toxin (BT) has been investigated, showing variable and sometimes conflicting results. Objectives: To compare the outcomes of bilateral BT injection and traditional surgery in a pediatric population with EIE in order to optimize and standardize the therapeutic approach. Other purposes are to evaluate whether early intervention may prevent the onset of vertical ocular deviation (which is part of the clinical picture of EIE) and/or influence the development of fine stereopsis, and also to assess changes in refractive status over time among the enrolled population. Methods: A retrospective consecutive cohort study was conducted in 86 children aged 0–48 months who underwent correction of EIE. The primary intervention in naïve subjects was either bilateral BT injection (36 subjects, “BT group”) or strabismus surgery (50 subjects, “surgery group”). Results: Overall, BT chemodenervation (one or two injections) was effective in 13 (36.1%) subjects. With regard to residual deviation angle, the outcomes at least 5 years after the last intervention were overlapping in children receiving initial treatment with either injection or surgery; however, the success rate of primary intervention in the surgery group was higher, and the average number of interventions necessary to achieve orthotropia was smaller. Both early treatment with chemodenervation and surgery at a later age were not found to prevent the onset of vertical ocular deviation, whereas, surprisingly, the percentage of subjects developing fine stereopsis was higher in the surgery group. Finally, with regard to the change in refractive status over time, most of the subjects increased their initial hyperopia, whereas 10% became myopic. Conclusions: Our data suggest that a single bilateral BT injection by age 2 years should be considered as the first-line treatment of EIE without vertical component; whereas, traditional surgery should be considered as the first-line treatment for all other cases and in subjects unresponsive to primary single BT injection.